2005
DOI: 10.1007/s00011-004-1318-5
|View full text |Cite
|
Sign up to set email alerts
|

A review of the action of tacrolimus (FK506) on experimental models of rheumatoid arthritis

Abstract: Tacrolimus (FK506) is an immunosuppressive drug, widely used for organ transplantation and atopic dermatitis. Tacrolimus exerts its immunosuppressive effects primarily by interfering with the activation of T cells, via inhibition of calcineurin. Recent clinical studies have also demonstrated the efficacy of tacrolimus in the treatment of rheumatoid arthritis (RA), an autoimmune disease in which T cells play a pivotal role in pathogenesis. Inflammatory cytokines such as TNF-alpha, IL-1 beta, and IL-6 are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 69 publications
(90 reference statements)
0
19
0
1
Order By: Relevance
“…TAC acts by binding to specific intracellular proteins. The formed complex inhibits calcineurin phosphatase, which prevents the activation of the transcription factor NF‐AT required for the production of cytokines, such as IL‐2 and γ‐interferon (Miyata et al, ). A clinical trial with TAC showed the advantages of combining it with MTX in treating patients with an inadequate response to MTX monotherapy (Kremer et al, ; Yocum et al, ; Kawai and Yamamoto, ).…”
Section: Discussionmentioning
confidence: 99%
“…TAC acts by binding to specific intracellular proteins. The formed complex inhibits calcineurin phosphatase, which prevents the activation of the transcription factor NF‐AT required for the production of cytokines, such as IL‐2 and γ‐interferon (Miyata et al, ). A clinical trial with TAC showed the advantages of combining it with MTX in treating patients with an inadequate response to MTX monotherapy (Kremer et al, ; Yocum et al, ; Kawai and Yamamoto, ).…”
Section: Discussionmentioning
confidence: 99%
“…CSA and FK506 have been employed in clinical graft-versus-host rejection after solid organ and bone-marrow transplantation over the past two decades. FK506 was recently approved in the USA for the treatment and prevention of immune-related diseases such as immune glomerulonephritis and rheumatoid arthritis [8,19]. A clinical study reported that FK506 could increase the level of serum albumin and reduce the level of urinary protein in the treatment of diffuse proliferative glomerulonephritis in associated with systemic lupus erythematosus [8].…”
Section: Discussionmentioning
confidence: 99%
“…This compound has also been introduced to treat atopic dermatitis for several years [4][5][6]. Some other new indications and applications of tacrolimus have been investigated as well [7,8]. There are quite a few published * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%